Gastrointestinal nematodes infections and anthelmintic resistance in grazing sheep in the Eastern Inner Mongolia in China - Han, Tianlong; Wang, Min; Zhang, Guanghe; Han, Dongsheng; Li, Xinwei; Liu, Guowen; Li, Xiaobing; Wang, Zhe (Acta parasitologica, 2017)
Gastrointestinal nematodes (GIN) are a crucial restraint to grazing sheep production worldwide. This study was conducted to determine the infections and anthelmintic resistance (AR) of GIN in pasture-based sheep in the Eastern Inner Mongolia, China. GIN eggs were tested from 600 grazing sheep feces of 10 farms using saturated saline flotation method and McMaster’s method. The egg hatch test (EHT) and the faecal egg count reduction test (FECRT) were used to evaluate resistance of GIN to anthelmintics. We found that the average infection rate was 79.2% (range: 45%–100%). The grand mean faecal egg count (FEC) was 1813.2 eggs per gram (EPG) (range: 0–32400 EPG). There were significant differences in GIN infection among different breeds of sheep. The sequence of infection intensity and infection rate were Small fat tail > Ujimqin > Ju Ud ( p <0.05). The 50% effective doses (ED 50 ) of albendazole(ABZ) and levamisole (LMS) for expelling were 5.670 μg/mL and 0.302 μg/mL, respectively. The percentage reductions of avermectin (AVM), ivermectin (IVM), ABZ and LMS were 81.28%, 86.49%, 76.21% and 96.59%, respectively. The most predominant parasite genus in all four anthelmintics was Haemonchus . In these tested areas, mixed infections of GIN in grazing sheep were very common. AR, especially in Haemonchus , was a serious problem in these sheep flocks. Thus, actions are urgently required to taken to mitigate the worsening situation.